Antioxidants in Health and Disease - Zampelas, Antonis; Micha, Renata (Taylor & Francis, 2015)
Antioxidants in Health and Disease discusses the effects of dietary antioxidants and antioxidant supplementation in humans. It reviews the latest evidence-based research in the area, principally through prospective cohort studies and randomized controlled trials. The book assesses major dietary antioxidants and discusses their use in diseases such as cancer, diabetes, stroke, coronary heart disease, HIV/AIDS, and neurodegenerative and immune diseases. The use of antioxidants in health is also discussed along with common adverse effects associated with antioxidant use. Separating myth from fact, this book gives you insight into the true role of antioxidants in health and disease.